A reliable measure of footwear upper comfort enabled by an innovative sock equipped with textile pressure sensors - Herbaut, A.; Simoneau-Buessinger, E.; Barbier, F.; Cannard, F.; Guéguen, N. (Ergonomics, 2016)
Footwear comfort is essential and pressure distribution on the foot was shown as a relevant objective measurement to assess it. However, asperities on the foot sides, especially the metatarsals and the instep, make its evaluation difficult with available equipment. Thus, a sock equipped with textile pressure sensors was designed. Results from the mechanical tests showed a high linearity of the sensor response under incremental loadings and allowed to determine the regression equation to convert voltage values into pressure measurements. The sensor response was also highly repeatable and the creep under constant loading was low. Pressure measurements on human feet associated with a perception questionnaire exhibited that significant relationships existed between pressure and comfort perceived on the first, the third and the fifth metatarsals and top of the instep.